Particle responses to negated assertions: Preference patterns for German ja and nein - Meijer, A. Marlijn; Claus, Berry; Repp, Sophie; Krifka, Manfred (Proceedings of the Amsterdam Colloquium, 2015)
The present study focusses on German polarity particles as responses to negative assertions. In such responses, the German response particles ja and nein are not used complementarily − similarly to their roughly corresponding English counterparts yes and no. Rather it seems that both ja and nein can be used to affirm a negative antecedent (e.g. A: Jim doesn’t snore. B: Ja./Nein. (=He doesn’t snore)). In a series of acceptability judgement experiments, we tested the predictions of two recent theoretical accounts (Krifka 2013 and Roelofsen and Farkas 2015). For affirming responses to negative assertions, both accounts predict a default preference for nein over ja. However, our experimental results revealed two subgroups of participants. A majority of approx. 70% showed a preference for ja over nein. The other subgroup showed a preference for nein over ja. To explain this finding, we consider modified versions of both accounts.